2011
DOI: 10.1128/jvi.02257-10
|View full text |Cite
|
Sign up to set email alerts
|

Prion Propagation in Cells Expressing PrP Glycosylation Mutants

Abstract: Infection by prions involves conversion of a host-encoded cell surface protein (PrP C ) to a disease-related isoform (PrP Sc ). PrP C carries two glycosylation sites variably occupied by complex N-glycans, which have been suggested by previous studies to influence the susceptibility to these diseases and to determine characteristics of prion strains. We used the Rov cell system, which is susceptible to sheep prions, to generate a series of PrP C glycosylation mutants with mutations at one or both attachment si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 64 publications
(93 reference statements)
2
38
0
Order By: Relevance
“…Their removal from an otherwise well tolerated insert indeed impaired prion replication ( Table 1, compare lanes 1 and 8 or lanes 5 and 9). Accordingly, substitution in wild-type PrP of the F or the T residues of the NFT glycosylation site was not always compatible with prion conversion 36 (see also Table 1). Another salient finding was that prion conversion also accommodated insertion of as much as 8 additional amino acids in the C-terminal region of H2 (Fig.…”
Section: Insertions In the H2-h3 Domain And Structural Models Of Prp Scmentioning
confidence: 99%
“…Their removal from an otherwise well tolerated insert indeed impaired prion replication ( Table 1, compare lanes 1 and 8 or lanes 5 and 9). Accordingly, substitution in wild-type PrP of the F or the T residues of the NFT glycosylation site was not always compatible with prion conversion 36 (see also Table 1). Another salient finding was that prion conversion also accommodated insertion of as much as 8 additional amino acids in the C-terminal region of H2 (Fig.…”
Section: Insertions In the H2-h3 Domain And Structural Models Of Prp Scmentioning
confidence: 99%
“…Rov cells are epithelial RK13 cells that stably express either wild-type or mutant ovine PrP using a tetracycline-inducible system (38,39). They were obtained by transfection and puromycin selection, grown in Opti-MEM medium (Invitrogen) supplemented with 10% fetal calf serum (FCS) and antibiotics, and split at 1:4 after trypsin dissociation once a week.…”
Section: Methodsmentioning
confidence: 99%
“…For PrP res , otherwise-indicated samples corresponding to the PK-resistant PrP present in either 25 or 50 g of protein of cellular lysate were loaded on the gel. The transfer of proteins, their detection, and their revelation were described previously (39,47).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial reports from studies in cell lines suggested that removing prion glycosylation produced spontaneously misfolded protein (Lehmann & Harris, 1997), however, this may have been a result of overexpression, since more recent studies have shown that blocking glycosylation of endogenously expressed PrP C does not produce this phenotype (Cancellotti, et al, 2005). In some cases, studies have been hampered by the folding and trafficking abnormalities that can occur when PrP C is expressed without glycosylation (Cancellotti, et al, 2005 depending on the specific mutations used to prevent glycosylation (Capellari et al, 2000, Ikeda et al, 2008, Salamat et al, 2011, Wong et al, 2000b. Neuendorf et al selected deglycosylating mutations that retained authentic PrP C cellular trafficking and mice in which these proteins were over-expressed were susceptible to both scrapie and BSE (Neuendorf et al, 2004).…”
Section: Factors Contributing To Prion Protein Misfoldingmentioning
confidence: 99%